2013
DOI: 10.18052/www.scipress.com/ilcpa.14.162
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Antioxidant Activity and Phytochemical Composition of Leaves Extract between Three Varieties of Date Palm Tree

Abstract: The date palm (Phoenyx dactylifera) consisted, for the people of southern Algeria, as tree of providence. Dates and their extracts are also used for many centuries as a medicine against allergy, inflammation, constipation and gastro-protective; they also have a high antibacterial and antioxidant activity. However, no studies are conducted to evaluate the extract from the leaves of date palm (Phoenyx dactylifera) in point of view of phytochemical composition, antimicrobial and the antioxidant activity. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…It is believed that the free radical scavenging activity of some medicinal plants is related to the phenolic compounds which contain phenols, flavonoids and tannins [19,20]. Our antioxidant results are in harmony with previous studies, which reported that the leaves of date palm have high antioxidant activity [21,22]. The antioxidant potency of the date palm leaf extracts could be attributed to the richness of these leaves in phytochemicals particularly phenols, the habitat, the environmental conditions, the biochemical and physiological processes of the plant [23].…”
Section: Resultssupporting
confidence: 90%
“…It is believed that the free radical scavenging activity of some medicinal plants is related to the phenolic compounds which contain phenols, flavonoids and tannins [19,20]. Our antioxidant results are in harmony with previous studies, which reported that the leaves of date palm have high antioxidant activity [21,22]. The antioxidant potency of the date palm leaf extracts could be attributed to the richness of these leaves in phytochemicals particularly phenols, the habitat, the environmental conditions, the biochemical and physiological processes of the plant [23].…”
Section: Resultssupporting
confidence: 90%
“…Kriaa et al [21] who studied the antioxidant activities of three varieties of DPL reported that the methanolic extracts showed total phenolics ranged between 69.06±0.41-146.46 ± 2.61mg caffeic acid equivalent (CAE)/g. Another study conducted by Eddine et al [22] reported that polyphenols content in three varieties of DPL was ranged from 156.46 ±4.21 to 215.24 ±9.25 mg GAE/g dry weight. The authors referred to that phenolic compounds content in DPL is influenced by several factors including water irrigation, soil, and environmental conditions.…”
Section: Total Phenolic and Total Flavonoid Content Of Dpl Extractsmentioning
confidence: 94%